Tinjauan Yuridis Perbuatan Melawan Hukum Penguasaan Rumah Toko Yang Merupakan Harta Warisan (Studi Putusan Nomor 215/Pdt/2017/PT. Medan) - Christian Situngkir; Zaini Munawir; Windy Sri Wahyuni (Universitas Medan Area, 2021)
Acting against the law is not only against the law, but also acts or does not violate the rights of others against decency or caution, appropriateness and propriety in public traffic. Actions against the law can also be interpreted as a collection of legal principles that aim to control or regulate dangerous behavior, to give responsibility for a loss that arises from social interactions, and to provide compensation to victims with an appropriate lawsuit. This type of research used in this paper is normative juridical. The research objective is to examine the juridical action against the law. The legal consequence of an illegal act committed on the basis of inheritance is that someone who commits an act against the law will be subject to sanctions in the form of compensation in accordance with the provisions in book III of the Civil Code which has been explained about Acts against the Law (PMH) starting from Article 1365 of the Civil Code up to Article 1380 KUHPerdata Legal settlement in unlawful acts committed on the basis of inheritance based on decision No. 215 / pdt / 2017 / PT. Mdn is settled by means of compensation that has been agreed between the parties and has been stated in the contents of the verdict of this case.